Metadiscourse in the academic writing of Malaysian and Arab pre-university students at the International Islamic University Malaysia - Muhamad Khairul bin Zakaria (Kulliyyah of Islamic Revealed Knowledge and Social Sciences, International Islamic University Malaysia, 2016)
Effective deployment of metadiscourse markers is one of the ways to improve writing quality. However, non-native writers seem to show lesser use of these markers. Therefore, this study examines the use of metadiscourse markers among 50 Malaysian and 50 Arab Pre-University students at the International Islamic University Malaysia to determine the frequency and forms of metadiscourse markers in the academic essays written by these students. The findings of this study indicated that there was a significant difference in the use of metadiscourse markers between Malaysian and Arab Pre-University student writers, χ2 (1, n = 100) = 7.17, p-value is .007 where the use of metadiscourse markers among Malaysian Pre-University students was substantially higher than that of the Arabs Pre-University students. A closer analysis revealed significant differences in the employment of interactive and interactional metadiscourse markers between the two groups. For the interactive metadiscourse markers, results showed significant differences between Malaysian and Arabs Pre-University writers in the use of transition, evidentials, and code glosses. Meanwhile, for the use of interactional metadiscourse markers, there were significant differences between Malaysian and Arabs Pre-University writers in the use of hedges, engagement markers and self-mentions. These variances in the frequency and forms of metadiscourse markers utilized could be attributed to the diverse cultural backgrounds of the two groups of students. Based on the observation that there were differences in the use of metadiscourse markers by the two groups, it was therefore suggested that English language teachers integrate cultural considerations in their syllabus with regard to metadiscourse markers. This could assist them in preparing teaching materials as well as in developing the students' awareness of the importance of these linguistic features.